Mechanically strong polyimide aerogels cross-linked with low-cost polymers. Issue 18 (15th March 2021) - Zhang, Zhongxin; Pan, Yuelei; Gong, Lunlun; Yao, Xiandong; Cheng, Xudong; Deng, Yurui
Abstract : Polyimide aerogels were prepared using low-cost polymers with different structure capped polyamide oligomers serving as cross-linking agents. Abstract : Polyimide aerogels were prepared using low-cost polymers with different structure capped polyamide oligomers serving as cross-linking agents. To investigate the effects of the anhydride density on cross-linker chain units and side groups of cross-linkers on their properties and microstructures, two kinds of polymers from maleic anhydride, endic anhydride, and styrene were prepared by simple radical polymerization. The polyimide aerogels exhibit densities as low as 0.087 g cm −3 and specific surface areas as high as 456 m 2 g −1 . And the maximum modulus of the aerogel is up to 21.3 MPa. These cross-linkers are alternatives to expensive small molecule cross-linkers, therefore reducing the cost of PI aerogels.